2020
DOI: 10.1016/j.jaci.2019.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of allergen powder for safe and effective epicutaneous immunotherapy

Abstract: Background: More effective and safer immunotherapies to manage peanut allergy are in great demand despite extensive investigation of sublingual/oral immunotherapy and epicutaneous immunotherapy (EPIT) currently in the clinics. Objective: We sought to develop a powder-laden, dissolvable microneedle array (PLD-MNA) for epidermal delivery of powdered allergens and to evaluate the efficacy of this novel EPIT in peanut-sensitized mice. Methods: PLD-MNA was packaged with a mixture of powdered peanut allergen (PNA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 52 publications
1
35
0
Order By: Relevance
“…Compared with the PBS-based patch, the oil-based patch could deliver more OVA into the skin. Confocal images showed that OVA had reached the interior of some cells, which had corresponding sizes and shapes to the APCs shown in a previous report [ 21 ]. In the images of skin sections, OVA was mainly found in the SC, and a smaller amount was found around hair follicles and in the upper dermis.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Compared with the PBS-based patch, the oil-based patch could deliver more OVA into the skin. Confocal images showed that OVA had reached the interior of some cells, which had corresponding sizes and shapes to the APCs shown in a previous report [ 21 ]. In the images of skin sections, OVA was mainly found in the SC, and a smaller amount was found around hair follicles and in the upper dermis.…”
Section: Discussionsupporting
confidence: 70%
“…At an MO concentration of 3% w / w and at 24 h of incubation, the proteins were not detected in the receptor medium; however, this is preferable in some cases such as antigen immunotherapy. In epicutaneous antigen immunotherapy, antigens are delivered only to the epidermis and are inhibited from entry to the dermis to prevent antigen delivery to the systemic circulation and thereby avoid acute severe immune reactions [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A novel EPIT based on dissolvable microneedle array (PLD‐MNA) coated with powdered peanut allergens mixed with 1,25‐dihydroxyvitamin D3 and CpG adjuvants (See Chapter 9) was recently evaluated for the treatment of peanut allergy in preclinical studies . Compared with intradermal EPIT, PLD‐MNA EPIT did not provoke any local skin inflammation.…”
Section: New Routes For Aitmentioning
confidence: 99%